BRAND ACTIVATION SEBAGAI BENTUK STRATEGI KOMUNIKASI PEMASARAN TERPADU (STUDI KASUS: HEADSTOCK COFFEE DI BALIKPAPAN) - Aji, Dandi Anggoro; Juwita, Rina (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
In the era of the development of information and communication technology, it is very influential in many business fields, one of which is the coffee shop business or often called a coffee shop. The purpose of this research is to find out brand activation as a form of integrated marketing communication strategy (Case study: Headstock Coffee in Balikpapan City). This research method is qualitative with a qualitative descriptive research type. The type of data used in this research is primary data including key informants and informants, as well as secondary data in the form of some literature such as books, journals, and several documents on the internet. Data analysis uses the concept of Miles and Huberman. The results of the research on presenting data on the application of Brand activation as a form of integrated marketing communication strategy at Headstock Coffee in Balikpapan are in the types of Brand activation namely, Direct marketing activation, Social media activation, Promotion activation, Marketing event activation, and Sponsorship activation supported by Integrated theory Marketing Communications (IMC) through several elements of marketing communications. In implementing Brand activation as an integrated marketing communication strategy, product marketing also needs to be strengthened so that Headstock Coffee's coffee shop business looks equal and even stands out from its marketing tool, namely Soundsreal space.